2007
DOI: 10.1248/bpb.30.1529
|View full text |Cite
|
Sign up to set email alerts
|

Delay in ICR/f Rat Lens Opacification by the Instillation of Eye Drops Containing Disulfiram and Hydroxypropyl-.BETA.-cyclodextrin Inclusion Complex

Abstract: Any alteration in the optical homogeneity of the lens or decrease in its transparency is known as a cataract, 1,2) and numerous factors have been implicated in its etiology, including genetic factors, diabetes, smoking, nutrition, the cumulative effect of X-rays, ultraviolet irradiation, and alterations in both endocrine and enzymatic equilibria.2-7) Currently, radical oxygen species, in particular, those induced by UV rays in sunlight, are considered to be important in perturbing lens homeostasis. Following e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…47) Therefore, in the in vitro skin penetration experiment, we used data collected in 0-30 h range to calculate the pharmacokinetic parameters. The amount of penetrated TL, the penetration rate (J c ), and the penetration coefficient through the skin (K p ) for the TL nano gel ointment were all significantly higher than those of the TL micro gel ointment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…47) Therefore, in the in vitro skin penetration experiment, we used data collected in 0-30 h range to calculate the pharmacokinetic parameters. The amount of penetrated TL, the penetration rate (J c ), and the penetration coefficient through the skin (K p ) for the TL nano gel ointment were all significantly higher than those of the TL micro gel ointment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…17) On the other hand, we also showed that a development of the DSF eye dropscontaininghigherthan0.5%wasimportantforstrongly inhibition of the lens opacification. However, high concentration of 2-hydroxypropyl-β-cyclodextrin need to prepare the solution containing high DSF amount (12% HPβCD need to preparethe1.4%DSFsolution),andthehighconcentrationof HPβCDcausetheirritationtocornea.…”
Section: Ddc Pharmacokinetics In Lens Following the Instillation Of Omentioning
confidence: 51%
“…We preciously prepared a 2-hydroxypropyl-β-cyclodextrin (HPβCD) solutioncontainingDSF(DSFsolution),andfoundthatitsinstillationdelayedlensopacificationinarecessive-typehereditary cataractous strain of rats (ICR/f and UPL rats). [17][18][19][20] In addition, we reported that the induction of inducible nitric oxide synthase (iNOS) via nuclear factor-kappa B (NF-κB) produces excessive nitric oxide (NO), and that this excessive NO causes enhanced lipid peroxidation and a decrease in cytochrome c oxidase in the lenses of hereditary cataractous strains of rats during cataract development. 18,19) The enhanced lipid peroxidation and decrease in cytochrome c oxidase lead to a decrease in Ca 2+ -ATPase function, resulting in lens opacification via the enhancement of Ca 2+ content in the lens.…”
Section: -5)mentioning
confidence: 99%
See 1 more Smart Citation
“…17) In a previous study, we prepared a HPβCD solution containing DSF and HPMC (DSF eye drops), and found that the instillation of these DSF eye drops delayed lens opacification in ICR/f rats, a recessive-type hereditary cataractous strain. 18,19) Therefore, it is possible that the antioxidant effect of DSF eye drops may provide a means to prevent or delay the formation of cataracts, and so it is very important to increase the efficacy of DSF eye drops. In this study, we attempted to enhance the delay effect of cataract development of DSF eye drops using low-substituted methylcellulose (MC, METOLOSE SM-4).…”
mentioning
confidence: 99%